New wealth for old nations : Scotland's economic prospects - Coyle, Diane; Alexander, Wendy; Aschroft, Brian, 1947- (Princeton University Press, 2005)
New Wealth for Old Nations provides a guide to policy priorities in small or regional economies. It will be of interest to policymakers, students, and scholars seeking avenues to improved growth, greater opportunity, and better governance. Some of the world's leading economists combine their research insights with a discussion of the practicalities of implementing structural reforms. Scotland is the ideal case study: the recent devolution of government in the United Kingdom offers a natural experiment in political economy, one whose lessons apply to almost any small, advanced economy. One fund.